The New Pattern of Online Credit Loan in the Post-Epidemic Era - Peng, Xiaozhun; Dong, Chenchen (The Economics and Finance Letters, 2021)
This paper is one of the few studies that discusses the impacts and challenges of banking business, especially online credit loans (also known as Internet loans or consumption loans) from the aspects of social environment, economic development, public policy, and technological environment changes under the impact of COVID-19 epidemic. Based on authors’ years of experiences in banking industry, they find that online loan products are facing with numerous problems, such as unclear position of online loan products, management dilemma of employees, dilemma between social responsibilities and debt collection, mismatch between risk and income, high bad-loan ratio issues and so on. To find effective ways to solve those problems, authors combined experience with practice and put forward several possible directions, such as seizing the opportunities of digital transformation to develop financial technology, expanding online products, establishing a new financial environment under changed consuming scene, and utilizing the strict supervision mechanism to expand traditional banking business.